Consumer’s Awareness of Global Warming and Its’ Impact on Purchasing Intention of Eco friendly Products - Ekidem, Mfonobong Essien (2010)
Human influence of the environment may generate changes that endanger various aspect of life on earth. The implications of reports about global warming and the effect it causes in the entire population is becoming intensely debatable but still awareness of the factors that contributes to global warming is still limited to consumers’. This study was conducted to examine consumers’ level of awareness of global warming and the impact on their purchase intentions of eco-friendly products. A survey method using self-administered questionnaire was use to gather data from consumers’. Result showed that media has a high influence of consumers awareness of global warming. The result also showed that level of awareness of global warming has a positive influence on consumers purchase intention of eco-friendly products. Recommendations and discussion for future study are provided.